The Prevalence Of Work-Related Musculoskeletal Problems And Ergonomic Risk Factors Among Women Production Line Employees In The Semiconductor Industry - S.Chandrasakaran, C.Abherhame (2001)
This cross-sectional study aimed to determine the work-related musculoskeletal problems of women production line employees in relation to their work postures and movements. At the beginning of the study in each of the eight factories, a walk-through survey was carried out to enable the researcher to understand the processes and tasks as well as to briefly observe the ergonomic risk factors (work postures and movements) . Women who were Malaysians, production line employees (up to the level of line leader) who were directly involved in production, and had worked for at least one year in the current factory were selected by the management of each factory for a questionnaire survey. A total of 529 respondents participated in the survey. The data was collected using a guided selfadministered questionnaire. Further i nformation was collected from a subsample of 330 women workers to obtain in-depth information about the description, severity and treatment of the most frequent body pain site.